Tinjauan Terhadap Profil Personaliti Pensyarah Universiti Penyelidikan - Abdul Rashid Abdul Aziz; Muhammad Khairi Mahyuddin; Nur Kareelawati Abd. Karim; Mohamad Yazid Abdul Majid; Nur A'in Mustafar; Nurun Najihah Musa (Secholian Publication, 2024)
Volume: 7, Issue: 10